PERAN PRODUSER DALAM PEMBUATAN MUSIC VIDEO “EVERYTHING GOES ON” (KOBO KANAERU REMAKE VERSION) - Josephine Stella; Arrya Dianta (Pojok Publisher, 2025)
The cultural landscape entering Indonesia is increasingly diverse, including music, cosplay, and virtual YouTube. This is evident in the abundance of animated and cosplay content on digital platforms. This topic is also supported by the development of new media. Content with a duration of less than 5 minutes is more frequently watched by the audience. A producer has the right to determine the story, supervise, and provide direction to the team. Therefore, the researcher, as producer, created a music video covering the song